Larvicidal Properties of the Essential Oils of Some Malaysian Plants on Three Vector Mosquitoes - Jantan, Ibrahim; Mohd Zaki, Zaridah; Ahmad, Rohani (Universiti Putra Malaysia Press, 1996)
The toxicity of the essential oils of eighteen Malaysian plants on the 4thinstar larvae of three vector mosquitoes (Anopheles maculatus, Aedes aegypti and Culex quinquejasciatus) was studied. The leaf oil of Litsea elliptica was the most effective, exhibiting LCso of 13.61 f-lg mr! for An. maculatus, 16.01 f-lg ml for Ae. aegypti and 14.63 f-lg ml for C. quinquejasciatus. The essential oils from the other species were also toxic with LCso ofl6.58 - 161.12 f-lg ml.